A Comparative Study of Mahāsi and Mogok Meditation Techniques in Myanmar - Ven. Vanasari (Wannasiri) (Journal of International Buddhist Studies, 2024)
This study investigates the popular use of the meditation techniques developed by Mogok and Mahāsi in Myanmar. Despite the fact that these two vipassana centres are well-known in Myanmar, research on a comparative analysis of these two widely used meditation techniques has been ignored in earlier studies. Since both the Mahāsi and Mogok meditation centres are thought to have very effective meditation methods, which is why many participants from both domestic and foreign countries find them to be relatively best destination, the author is especially interested in comparing their approaches. This study uses a qualitative research method consisting of an in-depth interview with a total of fourteen research subjects. Twenty research participants, consisting of laymen and monastic participants, were chosen from each center based on their participation in multiple meditation retreats conducted under the guideline of these two centres in Myanmar. This study aims to investigate and compare the meditation techniques of the Mogok and Mahāsi meditation centres located in Yangon, Myanmar. On the other hand, the outcome presents a relatively unique discovery that resulted from the study based on interviewees throughout the fieldwork. Furthermore, based on the four foundations of Buddhist meditation techniques, the study maintains that the two meditation techniques are almost identical. The only areas where techniques differ are in how they apply their unique methodologies and examples, which are briefly covered in the results section below.